1988
DOI: 10.1111/j.1476-5381.1988.tb11681.x
|View full text |Cite
|
Sign up to set email alerts
|

Quipazine reduces food intake in the rat by activation of 5‐HT2‐receptors

Abstract: 1 To determine which subtype(s) of 5-hydroxytryptamine (5-HT) receptor are involved in the anorectic action of quipazine, the ability of selective antagonists at 5-HT2-and 5-HT3-receptors, and an antagonist at 5-HT1-like receptors, to block this response were investigated in non-deprived rats, trained to eat a palatable diet. 2 Quipazine (0.5-8mg kg-, i.p.) produced a dose-related reduction in the intake of palatable diet. 3 The anorectic effect of 4 mg kg1 quipazine was antagonized by the nonselective 5-HT-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The failure of Aulakh et al (1989) (and RU 24969) and hence possibly also to their antagonists, than when food-deprived animals are used as in the present study (Table 3). A similar argument may also explain why doses of ketanserin and ritanserin needed to antagonize hypophagias induced by fenfluramine (Hewson et al, 1988), quipazine (Hewson et al, 1989) and DOI (Schechter & Simansky, 1988) were less than those we found to inhibit Kennett et al (1987) and Kennett & Curzon (1988a) expressed as percentages and Arcsin-transformed (Winer, 1971) as outlined by Bowman & Rand (1980). mCPP-induced hypophagia as these groups used fed rats exposed to a palatable diet.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The failure of Aulakh et al (1989) (and RU 24969) and hence possibly also to their antagonists, than when food-deprived animals are used as in the present study (Table 3). A similar argument may also explain why doses of ketanserin and ritanserin needed to antagonize hypophagias induced by fenfluramine (Hewson et al, 1988), quipazine (Hewson et al, 1989) and DOI (Schechter & Simansky, 1988) were less than those we found to inhibit Kennett et al (1987) and Kennett & Curzon (1988a) expressed as percentages and Arcsin-transformed (Winer, 1971) as outlined by Bowman & Rand (1980). mCPP-induced hypophagia as these groups used fed rats exposed to a palatable diet.…”
Section: Discussionsupporting
confidence: 68%
“…It is also relevant that the doses of ketanserin and ritanserin required for inhibition of hypophagia were much greater than those we found necessary for inhibition of 5-HT2 receptor-mediated head shakes. Furthermore, Neill & Cooper (1989) did not confirm the inhibitory effect of ketanserin on fenfluramine-induced hypophagia reported by Hewson et al (1988).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A variety of 5-HT 2 -selective agonists can exert stimulus control over behavior (Glennon 1991;Ismaiel et al 1993), and 5-HT 2 -selective agonists substitute for quipazine, whereas 5-HT 2 -selective antagonists readily block quipazine discrimination (Glennon et al 1983;Friedman et al 1984;Smith et al 1995). Moreover, studies have demonstrated 5-HT 2 receptor involvement in quipazine-induced suppression of schedule-controlled operant behavior in squirrel monkeys (McKearney 1990), and in quipazine-induced anorexia in rodents (Hewson et al 1988;Skukla et al 1990). In addition to serotonergic mechanisms, limited evidence indicates that DA could contribute to the discriminative-stimulus effects of quipazine.…”
Section: Discussionmentioning
confidence: 97%